Formy reglamentacji działalności gospodarczej w prawie łowieckim i ich warunki materialnoprawne - Boguszewska, Diana (Kwartalnik Prawa Publicznego, 2013)
Under the Constitution of the Republic of Poland economic activity is generally free and accessible for everyone; however regimentations of economic freedom might be imposed if significant public interest demands so. Such regimentations occur usually in form of the obligation to obtain a permission of public authority in order to carry out given economic activity. The article analysis the forms of regimentation of economic activity under the Hunting Law Act in relation to their scope and condition as well as makes an attempt to answer the question, if those forms effectively protect different categories of public interest they are dedicated to.